2006
DOI: 10.2214/ajr.05.0983
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 16-MDCT Angiography for Comprehensive Preoperative Vascular Evaluation of Laparoscopic Renal Donors

Abstract: 16-MDCT angiography enabled excellent preoperative detection of arterial anatomy and venous laparoscopic donor nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
47
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 30 publications
5
47
0
2
Order By: Relevance
“…In the present study, the smallest renal artery diameter found was 1.1 mm, and this value showed that the stated limitation is overcome by MSCT, especially 64-slice CT, due to the availability of the smallest (0.5 mm) thickness (6,7,10). In our study with a larger number of patients, the aRA prevalence of 22.8% was close to the prevalence found in a cadaveric study (2).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In the present study, the smallest renal artery diameter found was 1.1 mm, and this value showed that the stated limitation is overcome by MSCT, especially 64-slice CT, due to the availability of the smallest (0.5 mm) thickness (6,7,10). In our study with a larger number of patients, the aRA prevalence of 22.8% was close to the prevalence found in a cadaveric study (2).…”
Section: Discussionsupporting
confidence: 79%
“…In our study with a larger number of patients, the aRA prevalence of 22.8% was close to the prevalence found in a cadaveric study (2). These findings indicate that MSCT angiography provides results similar to those obtained for the conventional angiography technique (6,10,18,19).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations